The role of stakeholder involvement in the evolving EU HTA process: Insights generated through the European Access Academy’s multi-stakeholder pre-convention questionnaire - Lauren Van Haesendonck; Jörg Ruof; Thomas Desmet; Walter Van Dyck; Steven Simoens; Isabelle Huys; Rosa Giuliani; Mondher Toumi; Christian Dierks; Juliana Dierks; Antonella Cardone; Francois Houÿez; et al. (Journal of Market Access & Health Policy)
ABSTRACTInvolvement of all relevant stakeholders will be of utmost importance for the success of the developing EU HTA harmonization process.A multi-step procedure was applied to develop a survey across stakeholders/collaborators within the EU HTA framework to assess their current level of involvement, determine their suggested future role, identify challenges to contribution, and highlight efficient ways to fulfilling their role. The ‘key’ stakeholder groups identified and covered by this research included: patients‘, clinicians‘, regulatory, and Health Technology Developer representatives. The survey was circulated to a wide expert audience including all relevant stakeholder groups in order to determine self-perception by the ‘key’ stakeholders regarding involvement in the HTA process (self-rating), and in a second, slightly modified version of the questionnaire, to determine the perception of ‘key’ stakeholder involvement by HTA bodies, payers, and policymakers (external rating). Predefined analyses were conducted on the submitted responses.Fifty-four responses were received (patients 9; clinicians: 8; regulators: 4; HTDs 14; HTA bodies: 7; Payers: 5; policymakers 3; others 4). The mean self-perceived involvement score was consistently lower for each of the ‘key’ stakeholder groups than the respective external ratings. Based on the qualitative insights generated in the survey, a RACI Chart (Responsible/Accountable/Consulted/Informed) was developed for each of the stakeholder groups to determine their roles and involvement in the current EU HTA process.Our findings suggest extensive effort and a distinct research agenda are required to ensure adequate involvement of the key stakeholder groups in the evolving EU HTA process.